Fire Safety Risk Assessment of Workplace Facilities: A Case Study - Hassanain, Mohammad A.; Al-Harogi, Mohammed; Ibrahim, Ahmed M. (Frontiers in Built Environment, 2022)
Workplace facilities are organizational capital assets, which entail high risks of fire occurrences. The fire risks increase based on occupants’ behaviours, lack of awareness and poor workspaces safety management. Thus, fire safety risk assessment is vital to raise awareness about workplace fire-safety culture, and to train employees on effective fire response requirements and methods. The literature lacks studies focusing on managing fire safety at the workplace, and limiting occupants dispossessed behaviours. This research presents a case study, which demonstrates the utilization of risk assessment for fire safety prevention in a workplace facility. Relevant literature is synthesized for identifying causes of fire, various propagation hazards, control measures to develop a risk assessment tool based on fire codes. The codes were analysed by describing the requirements for fire safety precautionary measures, followed by an exemplary assessment. This research aims to provide professional practice and knowledge on fire risk assessment methodology, serving safety professionals, and facilities managers. It serves to raise awareness on the causes of fire, consequences of fire events, and mitigation strategies in workplace facilities, for the purpose of protecting users’ lives and business properties against fires.